Hodnocení finanční situace podniku a návrhy na její zlepšení - Khýrová, Michaela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Bakalářská práce se zaměřuje na hodnocení finanční situace výrobní společnosti Toray Textiles Central Europe s.r.o. Cílem práce je identifikovat silné a slabé stránky finančního zdraví a navrhnout opatření pro zlepšení situace. Teoretická část definuje základní pojmy a teoretická východiska z odborné literatury, volená s ohledem na charakteristiku podniku. V analytické části jsou použity zvolené metody a postupy, na jejichž základě jsou vytvořena doporučení pro zlepšení finanční situace společnosti.

The bachelor production thesis focuses on the evaluation of the financial situation of the company Toray Textiles Central Europe s.r.o. The aim of the work is to identify the strengths and weaknesses of financial health and propose measures to improve the situation. The theoretical part defines the basic concepts and theoretical starting points from the professional literature, chosen with regard to the characteristics of the company. In the analytical part, selected methods and procedures are used, on the basis of which recommendations are made for improving the company's financial situation.
Evaluation of the Financial Situation of a Company and Proposals for its Improvement
Keywords: hodnocení finanční situace; ukazatele finanční analýzy; finanční analýza; Porterův model pěti sil; SLEPTE analýza; návrhy pro optimalizaci; assessment of the financial situation; indicators of financial analysis; financial analysis; Porter's five forces model; SLEPTE analysis; suggestions for optimization